IMPOLITENESS STRATEGIES APPEARED IN PEAKY BLINDERS SERIES - Nanda Dea Milinea Sitio; Yenti -; Putri Ayu Lestari (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
This research discusses the impoliteness strategies in Peaky Blinders Series 2017. Peaky Blinders Series told story the life of a group of dangerous gangsters in Birmingham, England. The purposed of this study were as follows to describe the types of impoliteness strategies appeared in Peaky Blinders Series, to explain the reasons of the characters in Peaky Blinders Series used impoliteness strategies, to describe the types of responses to the impoliteness among characters. This research used a pragmatic approach from Leech (1989) , impoliteness strategy by Culpeper (2003), Culpeper (2011) and Magford (2008). The method used qualitative descriptive method to analyzed the data, the researchers used documentation to collect the data, source of data was taken from the dialogues and scene in Peaky Blinders Series 2017. The findings in this research showed that the characters in Peaky Blinders Series 2007 used impoliteness strategy to communicate with others characters. (1) there were three types of impoliteness strategies used by selected characters were bald on record, positive impoliteness, and negative impoliteness, and (2) the reason why the selected characters used impoliteness strategies were social status, social distance or familiarity, and situation.